TRAINING CENTRAL ASIAN JOURNALISTS: OVIET LEGACIES MEET LESSONS FROM U.S. EDIA HISTORY - FREEDMAN, Eric; SHAFER, Richard; RICE, Gary (CENTRAL ASIA AND THE CAUCASUS, 2006)
western governments, international development agencies, foundations, and donor organizations regard “democratic journalism” as a tool to liberalize authoritarian re gimes and contain religious fundamentalism and anti-Western sentiments abroad. It has become synonymous with Western-style journalism and is regarded as dedicated to extending democracy and free market economics. Since the Soviet Union collapsed in 1991, democratic journalism has been exported to its former republics through seminars and workshops that generally emphasize traditional U.S. news values such as impact, conflict, novelty, prominence, proximity, and timeliness.1 As journalism educators and trainers, we have participated in this process. These values are often touted as alternatives to values connected to Soviet-era news conventions, policies, and underlying ideology.There is no generally accepted definition of “democratic journalism,” but commonly accepted elements are drawn from the libertarian press model of Siebert, Peterson, and Schramm. Although the relevance of their Cold War-era categorization may be outdated, as critics2 argue, their model includes identifiable attributes of “democratic journalism:” “The press is conceived of as a partner in the search for truth… The press is not an instrument of government, but rather a device for presenting evidence and arguments on the basis of which the people can check on government and make up their minds as to policy. Therefore, it is imperative that the press be free from government control and influence… There must be a ‘free market place’ of ideas and information.